Testicular Germ Cell Tumors Type 2 Have High Rna Expression of Ldhb, the Gene for Lactate Dehydrogenase Subunit B - Parraga-Alava, J (Wolters Kluwer Medknow Publications, 2021)
This study analyzed RNA expression of genes for three serum tumor markers, alpha fetoprotein (AFP), human chorionic gonadotropin (hCG), and lactate dehydrogenase (LDH), in patients with testicular germ cell tumors (TGCT) type 2. The gene AFP encodes AFP, the gene for chorionic gonadotropin beta polypeptide 5 (CGB5) encodes a major part of the specific beta subunit of hCG, and the genes for LDH subunit A (LDHA), LDH subunit B (LDHB), and LDH subunit C (LDHC) encode three different subunits of LDH. LDHB encodes the LDHB subunit present as a tetramer in LDH isoenzyme 1 (LDH-1). We examined three datasets with 203 samples of normal testis tissue (NT) and TGCT type 2. Yolk sac tumor (YST) expressed RNA of AFP fourteen thousand times higher than seminoma (SE), embryonal carcinoma (EC), and teratoma (TER) combined (P = 0.00015). In the second microarray, choriocarcinoma (CC) expressed RNA of CGB5 ten times higher than other histologic types of TGCT combined. EC expressed RNA of LDHB twice higher than SE, YST and TER combined (P = 0.000041). EC expressed RNA of LDHB higher than that YST expressed RNA of AFP and that CC expressed RNA of CGB5. In conclusion, TGCT type 2 expressed RNA of LDHB markedly higher than the RNA of 23 other candidate genes for TGCT type 2. © 2021 Wolters Kluwer Medknow Publications. All rights reserved.